The congruency between home and school literacy practices in a South African primary school - McNamara, Lynne (My University, 2014)
South Africa has undergone widespread changes in the educationni system and previously racially segregated schools have been opened to all races unce the early 1990's. The new multi-cultural composition of many suburban schools has raised the question of the extent of congruence between school literacy practices and those in households originating in different cultural contexts. Accordingly, this study examined the congruence between home and school literacy practices and values and its impact on scholastic achievement. A broad literature survey was conducted which distinguished three streams of research and theory, namely the cognitive stream, the educational stream and the socio-cultural stream. The socio-cultural paradigm was adopted to examine the literacy practices of diverse cultural groups. Reference was also made to interactive information-processing models and schema theory. An appropriate multi-cultural school was identified for observation of dominant sociocultural values, specific school literacy practices, discourse patterns and expectations of parental involvement in the children's education. Ten children in two classes were selected for further study on the basis of geographical, racial, cultural and economic diversity, school achievement and parental interest in schooling. Children from both the suburbs and the townships were included, together with a mixed category comprising township families who had recently moved into the suburbs, the child of a domestic servant and a black child who lived with a white suburban family. A number of themes were explored in the home context and related to school performance, namely socio-cultural identity and values, parental role and support in schooling, discourse patterns, literacy practices and availability of resources. The main findings of the research were firstly that socio-cultural values provided a broad context for achievement, although the lack of value congruence affected only a few children. Secondly, middle-class family literacy practices were congruent with school literacy practices and the children of these families all performed well at school. However, certain students could perform scholastically in spite of a lack of congruence in literacy practices, provided they had parental support. Thirdly, children from a variety of socio-economic and cultural contexts who received direct curricular assistance with homework achieved average or above average results at school. However, the direct help which they received may only have short-term positive effects on school achievement because the children did not acquire the background schemas to enable generalization and integration. Finally, in middle-class households where a broad literate orientation was adopted, and where the parents provided extended, decontextualised support beyond the curriculum, more generalized changes in thinking were likely to occur, with these children more likely to deal effectively with new learning situations and incorporate new information. In conclusion, it is argued that congruency needs to go beyond literacy practices and values to embrace broader school and home values. Suggestions are made for achieving greater congruency by effecting changes in practices and values in the classroom and the home.